Fracture toughness of welding alloy in ductile cast iron - Bressan J.D.* (2009)
Nowadays, there are few research and knowledge about fracture in welded ductile iron. Service life of mechanical components is limited by fracture due to the presence of high stresses, low fracture toughness and cracks. Welded parts may have a weakened region or the HAZ (heat-affected zone) due to the welding process in which martensite can be formed and it is brittle. Present work examines the critical stress intensity factor K1C of welded ductile cast iron, using a Fe-Ni-Mn alloy as weld and the three point bending test of a notched beam, or SENB specimen, performed according to the ASTM E399 and E561 standards. Initially, a pre-crack was generated by fatigue in a notched specimen, assembled in the specially fabricated mechanical equipment developed in laboratory. Plane strain fracture testing method of Linear Elastic Fracture Mechanics and the compliance method of Non-linear Fracture Mechanics were applied to calculate the fracture toughness K1C. In addition, Charpy impact testing of notched specimens where also carried out to evaluate and compare the rupture energy for the welded and non-welded specimens with K 1C: an experimental correlation is presented. The material microstructures were characterised by micrographs obtained from optical microscope and the fractured surface was examined by SEM (Scanning Electron Microscope) photographs. The obtained mean value of fracture toughness K IC for ductile iron was 37 MPa.m1/2 and weld metal alloy was 54.1 MPa.m1/2, however for the specimens with pre-crack at the HAZ the mean fracture toughness was 31 MPa.m1/2. The different fracture mechanisms are also shown and discussed.